1990
DOI: 10.1159/000205184
|View full text |Cite
|
Sign up to set email alerts
|

HLA Antigens and Haplotypes Associated with Idiopathic Haemochromatosis in Veneto: Peculiar Association with HLA-A3, B35

Abstract: HLA-A and HLA-B antigens were determined in 16 unrelated subjects orginating from Veneto affected by idiopathic haemochromatosis (IH). HLA-A3 was found in 13/16 patients vs. 300/1,348 controls (p < 0.00005). Prevalences of A3, B35 haplotype were 0.4375 in patients vs. 0.0816 in controls (p < 0.0005). Linkage disequilibrium analysis proved the existence of a positive third-order linkage disequilibrium among IH, HLA-A3 and HLA-B35 alleles. Our data confirm the close association of IH and HLA-A3 and prove the pec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…We also found that the HLA-A*03-B*35 haplotype associated with the H63D mutation is increased in the studied population. Interestingly, the HLA-A*03-B*35 has been linked to hemochromatosis in north-eastern regions of Italy ( Panajotopoulos et al , 1989 ; De Menis et al , 1990 ), but not so in Spain, where there is a significant association between the HLA-A*03-B*62 and HLA-A*03-B*44 haplotypes and the C282Y mutation ( Pacho et al. , 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the HLA-A*03-B*35 haplotype associated with the H63D mutation is increased in the studied population. Interestingly, the HLA-A*03-B*35 has been linked to hemochromatosis in north-eastern regions of Italy ( Panajotopoulos et al , 1989 ; De Menis et al , 1990 ), but not so in Spain, where there is a significant association between the HLA-A*03-B*62 and HLA-A*03-B*44 haplotypes and the C282Y mutation ( Pacho et al. , 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Haemochromatosis is particularly associated with HLA-A3, B7, B14 (Milman et al, 1994). The HLA association vanes geographically (De Menis et al, 1990;Milman et al, 1992), such that haemochromatosis in central Sweden, England and Ireland is A3, B 14 dominated, while in Australia, Central Europe, USA and Canada it is associated with HLA-A3, B7. Both of our patients showed the Australian HLA-A3, B7 association.…”
Section: Discussionmentioning
confidence: 99%